The impact of craft creation practice on university students’ mental health: a moderated network analysis - Jiang, Xuejie; Lu, Xunzhou; Pu, Meihe; Li, Xiaowen (Frontiers in Public Health, 2025)
IntroductionThere has been relevant research on the effectiveness of craft creation practices (CCP) on the mental health of university students. However, little is known about the potential mechanisms affecting the network structure of mental health under the dual-factor model.MethodsThis study employs moderated network analysis methods (MNM) to explore the reorganization of connections between various mental health indicators after craft creation practices. The study involved 353 university students from Anhui Province, who were randomly assigned to an intervention group (n = 185) or a control group (n = 229) to participate in an 8-week, 48-h craft creation practice.ResultsThe results showed changes in the network structure of different mental health variables after the intervention. Unlike the control group participants, social well-being was negatively correlated with depression and stress.ConclusionThis study supports the feasibility of using network approaches to analyze the connections between mental health indicators defined by a two-factor model and the contribution of craft creation practices to altering the complex relationship patterns between positive and negative psychological dimensions.